Plant immunity to insect herbivores: mechanisms, interactions, and innovations for sustainable pest management - Vasantha-Srinivasan, Prabhakaran; Noh, Mi Young; Park, Ki Beom; Kim, Tae Yoon; Jung, Woo-Jin; Senthil-Nathan, Sengottayan; Han, Yeon Soo (Frontiers in Plant Science, 2025)
Plant–insect interactions pose a major threat to global food security and ecological stability. This review provides a comprehensive synthesis of the molecular and physiological mechanisms underlying plant immunity against herbivorous insects, with emphasis on structural defenses, secondary metabolites, and hormone signaling pathways including Jasmonic acid, salicylic acid, and ethylene. It highlights key advances in understanding defense signaling crosstalk, effector-triggered responses, and the role of microbiota and environmental cues. The review further discusses insect counterstrategies and explores cutting-edge technologies-CRISPR/Cas9, RNA interference, and metabolic engineering that are reshaping pest management. However, challenges remain, including limited field validation of engineered traits, ecological trade-offs, and regulatory hurdles. We conclude by outlining future research directions focused on multi-omics integration, climate-resilient defense networks, and ethical deployment of plant biotechnologies within sustainable agroecosystems.